Exploring cellular behavior under transient gene expression and its impact on mAb productivity and Fc‐glycosylation. Issue 2 (16th November 2017) - Sou, Si N.; Lee, Ken; Nayyar, Kalpana; Polizzi, Karen M.; Sellick, Christopher; Kontoravdi, Cleo
Abstract: Transient gene expression (TGE) is a methodology employed in bioprocessing for the fast provision of recombinant protein material. Mild hypothermia is often introduced to overcome the low yield typically achieved with TGE and improve specific protein productivity. It is therefore of interest to examine the impact of mild hypothermic temperatures on both the yield and quality of transiently expressed proteins and the relationship to changes in cellular processes and metabolism. In this study, we focus on the ability of a Chinese hamster ovary cell line to galactosylate a recombinant monoclonal antibody (mAb) product. Through experimentation and flux balance analysis, our results show that TGE in mild hypothermic conditions led to a 76% increase in qP compared to TGE at 36.5°C in our system. This increase is accompanied by increased consumption of nutrients and amino acids, together with increased production of intracellular nucleotide sugar species, and higher rates of mAb galactosylation, despite a reduced rate of cell growth. The reduction in biomass accumulation allowed cells to redistribute their energy and resources toward mAb synthesis and Fc‐glycosylation. Interestingly, the higher capacity of cells to galactosylate the recombinant product in TGE at 32°C appears not to have been assisted by the upregulation of galactosyltransferases (GalTs), but by the increased expression of N‐acetylglucosaminyltransferase II (GnTII) in this cell line, which facilitated the production of bi‐antennary glycan structures for further processing. Abstract : Introducing mild hypothermia during transient gene expression changes the quality of the recombinant protein produced. The specific galactosylation capacity of cells is higher at 32°C due to the higher production of bi‐antennary structures for further processing.